Calcified pericardial band at the level of right ventricle causing midventricular obstruction: a case report of constrictive pericarditis - Gautam, MP; Sharma, D; Subramanyam, G; Gautam, S; Ghimire, U (Journal of College of Medical Sciences-Nepal, 2012)
Constrictive pericarditis is a debilitating but potentially curable disease. Diffuse pericardial thickening and calcification is a classic feature described; localized pericardial constrictions are very rare. Here we report a case of a young female who had presented with constrictive pericarditis and had localized calcific constrictive band located at the level distal to atrioventricular groove which had caused right midventricular obstruction. In many patients the cause of the pericardial disease is undetermined, and in them an asymptomatic or forgotten bout of viral or tubercular pericarditis, acute or idiopathic, may have been the inciting event. Our patient had pulmonary tuberculosis during childhood and received antituberculous treatment. Investigations revealed the presence of thickened pericardium and a thickened calcific constrictive band around the right ventricles at midventricle level causing midventricular obstruction. She was referred to another centre for further surgical management. Journal of College of Medical Sciences-Nepal,2011,Vol-7,No-4, 58-62 DOI: http://dx.doi.org/10.3126/jcmsn.v7i4.6813